1994
DOI: 10.1093/infdis/170.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Disease Caused by Neisseria meningitidis Relatively Resistant to Penicillin in North Carolina

Abstract: A case of sepsis and meningitis caused by Neisseria meningitidis with relative resistance to penicillin occurred in North Carolina in August 1992. This isolate was relatively resistant due to decreased affinity of its penicillin-binding protein 2 for penicillin. Such isolates have been reported in Spain, elsewhere in Europe, in South Africa, and in Canada, but invasive disease caused by meningococcal isolates relatively resistant to penicillin was not recognized in the United States before a preliminary report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…Penicillin is used effectively in the treatment of meningococcal infections; however, strains with decreased susceptibility to penicillin (MICs, Ͼ0.06 g/ml) have been reported in several countries (8,11,20,44,49), and some studies have shown that decreased susceptibility has been linked to a single clone (13,38). The clinical significance of this increased resistance is unknown, and infections with these strains appear to respond to penicillin therapy (44).…”
mentioning
confidence: 99%
“…Penicillin is used effectively in the treatment of meningococcal infections; however, strains with decreased susceptibility to penicillin (MICs, Ͼ0.06 g/ml) have been reported in several countries (8,11,20,44,49), and some studies have shown that decreased susceptibility has been linked to a single clone (13,38). The clinical significance of this increased resistance is unknown, and infections with these strains appear to respond to penicillin therapy (44).…”
mentioning
confidence: 99%
“…Penicillin has historically been an effective antibiotic, but strains with reduced susceptibility to penicillin (often referred to as relatively resistant or penicillinintermediate strains) have been reported in Europe, South America, Asia, Australia, and, less frequently, in the United States (3,7,17,21,23,24,30,32,36,38). Such strains have been shown to have alterations in penicillin-binding protein 2 (PBP2; encoded by the penA gene), thought to be the result of formation of mosaic genes derived through transformation with DNA from commensal Neisseria species in the nasopharynx of colonized individuals (2,33).…”
mentioning
confidence: 99%
“…Sáez Nieto et al (1997) described an increase of meningococcal strains showing MICs between 0.12 and 1 mg/l from 0.4% in 1985 and reaching 42.6% in 1990. Such isolates have been reported elsewhere in Europe, in South Africa, and in Canada (Woods et al 1994). Six meningococci, isolated from patients and carriers during a large epidemic of meningococcal meningitis in Malawi had MICs of penicillin (> or = 2 mg/l) high enough to render them clinically resistant (Bellete et al 1994).…”
mentioning
confidence: 71%